Comparative evaluation of palm-based carotene microcapsules produced via spray drying and supercritical fluid drying and their application as a non-dairy creamer - Liau, Khai Yi; Liu, Yan; Zhao, Yiguo; Tan, Tai Boon (Springer, 2025)
Numerous studies have explored the encapsulation of pure carotenes, but the high cost and non-sustainability of pure carotene extracts limit their use. This study addressed these limitations by encapsulating sustainable, palm-based carotene using plant-based wall materials; modified waxy maize starch (MS), soy protein isolate (SPI), and gum Arabic (GA) at varying oil-to-wall materials ratios (1:1.5, 1:2, 1:3). Microencapsulation was achieved using spray drying and solution-enhanced dispersion by supercritical carbon dioxide (SEDS) techniques. Among all formulations, spray-dried M-MS at a 1:3 ratio achieved the highest carotene retention and microencapsulation efficiency (51.29%), while SEDS-M-MS exhibited significantly higher microencapsulation efficiency (95.88%) but lower carotene retention. The oil-to-wall ratios significantly influenced physicochemical properties, including moisture content (1.85–3.47% for spray-dried vs. 8.22% for SEDS), water activity (0.09–0.54), and flowability (CI as low as 18.17%). Both M-MS 1:3 and SEDS-M-MS microcapsules were successfully incorporated as non-dairy creamer (NDC) in black coffee, resulting in significant improvements in pH (from 4.72 ± 0.11 to ≥ 5.02 ± 0.01) and lightness (L* from 23.56 ± 0.34 to ≥ 27.04 ± 0.87), signifying good techno-functional (acidity softening and whitening capacities) properties. Sensory evaluation revealed no significant differences (p > 0.05) in color and appearance between coffees with commercial and prepared NDCs. These results indicate that spray-dried M-MS 1:3 microcapsules offer optimal techno-functional performance, while SEDS could be a promising sustainable alternative for the production of microcapsules containing oil-soluble bioactive compounds.